Chinese Lending to Sri Lanka: A Factual cum “Reality” Check A Rejoinder to Umesh Moramudali and Thilina Panduwawala - Sarvananthan, M. (Social Science Research Network, 2023)
This is a response to the Briefing Paper entitled Evolution of Chinese Lending to Sri Lanka since the mid-2000s – Separating Myth from Reality, written by Umesh Moramudali and Thilina Panduwawala published by the China-Africa Research Initiative of the School of Advanced International Studies (SAIS) at the John Hopkins University, USA. This response identifies a few factual errors (both quantitative and qualitative) and provides alternative data, and contests the interpretations of the data and conclusion drawn therefrom by Moramudali and Panduwawala by providing concrete examples to the contrary. We characterise Chinese lending to Sri Lanka between 2007 and 2022 as quasi-predatory lending, having defined the characteristics of predatory lending.
Keywords: China; Hambantota Port; Predatory Lending; Sovereign Default; Sri Lanka